Adsorption of Cr(OH)n(3−n)+ (n = 1–3) on Illite (001) and (010) Surfaces: A DFT Study - Jia Du (MDPI AG, 2021)
The development of clay adsorption materials with high Cr(III) removal capacities requires an understanding of the adsorption mechanism at the atomic level. Herein, the mechanisms for the adsorption of Cr(OH)2+, Cr(OH)2+, and Cr(OH)3 on the (001) and (010) surfaces of illite were studied by analyzing the adsorption energies, adsorption configurations, charges, and state densities using density functional theory (DFT). The adsorption energies on the illite (010) and (001) surfaces decrease in the order: Cr(OH)2+ > Cr(OH)2+ > Cr(OH)3. In addition, the energies associated with adsorption on the (010) surface are greater than those on the (001) surface. Further, the hydrolysates are highly active and can provide adsorption sites for desorption agents. The silica (Si–O) ring on the illite (001) surface can capture Cr(OH)n(3−n)+ (n = 1–3). In addition, both Cr(OH)2+ and Cr(OH)2+ form one covalent bond between Cr and surface OS1 (Cr–OS1), whereas the hydroxyl groups of Cr(OH)3 form three hydrogen bonds with surface oxygens. However, increasing the number of hydroxyl groups in Cr(OH)n(3−n)+ weakens both the covalent and electrostatic interactions between the adsorbate and the (001) surface. In contrast, the Cr in all hydrolysates can form two covalent Cr–OSn (n = 1–2) bonds to the oxygens on the illite (010) surface, in which Cr s and O p orbitals contribute to the bonding process. However, covalent interactions between the cation and the (010) surface are weakened as the number of hydroxyl groups in Cr(OH)n(3−n)+ increases. These results suggest that the illite interlayer can be stripped to expose Si–O rings, thereby increasing the number of adsorption sites. Furthermore, regulating the generated Cr(III) hydrolysate can increase or weaken adsorption on the illite surface. Based on these findings, conditions can be determined for improving the adsorption capacities and optimizing the regeneration performance of clay mineral materials.